Human Existential Desire for Immortality in Unamunoas Perspective (Global Journal of Human-Social Science, 2012)
Human existential desire for immortality of the soul has been a persistent philosophical problem down the ages such that it is imperative for different thinkers to hold divergent opinions in their genuine search for the truth Unamuno in his sincere search for the truth of immortality firstly tries rationalism thereby tending towards Hegelianism When he sees that the power of human reason cannot express the inexpressible the cardinal inherent human hunger thirst and desire for self-perpetuation and self-preservation the longing not to die but to live forever he turns to irrationalism In other words Unamuno claiming that man has eternal soul substantiates his thesis of immortality of the human soul merely via the method of irrationalism Is this sufficient Therefore the paper exposes different views on the immortality of the soul and assesses Unamuno s method of enquiry and further clarifies his notion of immortality of the soul It proposes a synthesis of rationalism and irrationalism as a solution in explaining the concept in question which provides more rooms for the different dimensions of interpretations one might offer to the problem of immortality of the soul The paper illumines people s minds on the problem of human existence and enlightens humanity to live meaningful life here for the hereafter To discover death is to discover the hunger of immortality Unamuno Tragic Sense of Life
Keywords: desire; existential; immortality; perspective